Electric field effect surface passivation for silicon solar cells - Bonilla, R; Reichel, C; Hermle, M; Wilshaw, P (Trans Tech Publications Ltd, 2014)
Effective reduction of front surface carrier recombination is essential for high efficiency silicon solar cells. Dielectric films are normally used to achieve such reduction. They provide a) an efficient passivation of surface recombination and b) an effective anti-reflection layer. The conditions that produce an effective anti-reflection coating are not necessarily the same for efficient passivation, hence both functions are difficult to achieve simultaneously and expensive processing steps are normally required. This can be overcome by enhancing the passivation properties of an anti-reflective film using the electric field effect. Here, we demonstrate that thermally grown silicon dioxide is an efficient passivation layer when chemically treated and electrically charged, and it is stable over a period of ten months. Double layers of SiO2 and SiN also provided stable and efficient passivation for a period of a year when the sample is submitted to a post-charge anneal. Surface recombination velocity upper limits of 9 cm/s and 19 cm/s were inferred for single and double layers respectively on n-type, 5 ωcm, Cz-Si. © (2014) Trans Tech Publications, Switzerland.